Randomised trial of Aureobasidium pullulans-produced beta 1,3-1,6-glucans in patients with Duchenne muscular dystrophy: favourable changes in gut microbiota and clinical outcomes indicating their potential in epigenetic manipulation - Naoki Yamamoto; Kadalraja Raghavan; Vidyasagar Devaprasad Dedeepiya; Nobunao Ikewaki; Masaru Iwasaki; Senthilkumar Preethy; Rajappa Senthilkumar; Samuel J K Abraham; Ashwamed Dinassing (BMJ Nutrition, Prevention & Health)
Objective Duchenne muscular dystrophy (DMD) is an X-linked neuromuscular disorder that leads to increasing muscle weakening and early death. Steroids, the standard treatment of choice in slowing down disease progression, are plagued with adverse effects. Anti-inflammatory, antifibrotic effects and enhancement of muscle regeneration biomarkers after oral consumption of Aureobasidium pullulans strain N-163-produced beta 1,3–1,6-glucan (Neu REFIX) having been demonstrated in clinical and preclinical studies of DMD; in this study, we have investigated the effects on the gut microbiome in patients with DMD.Design Twenty-seven patients with DMD were included in the study (control (n=9), N-163 (n=18)). Whole-genome metagenomic sequencing was performed in pre-N-163 and post-N-163 intervention faecal samples of each of these participants.Results After N-163 beta-glucan administration, the constitution of the gut microbiome in all the participants was modified to one with positive outcomes on health. There was an increase in butyrate-producing species such as Roseburia and Faecalibacterium prausnitzii. There was a decrease in harmful bacteria associated with inflammation such as enterobacteria and Alistipes.Conclusion Beneficial reconstitution of the gut microbiome after Neu REFIX beta-glucan administration and its safety have been confirmed. These outcomes correlating with the anti-inflammatory, anti-fibrotic effects along with increase in dystrophin in skeletal muscle and plasma, reported earlier make us recommend further in-depth exploration on its role in epigenetic manipulation which when found encouraging might help other genetic diseases as well.Trial registration number CTRI/2021/05/033346.